Productive and physiological behavior of fattening sheep with supplementation while grazing on Brachiaria spp. (Revista Sistemas de Producción Agroecológicos, 2024)
Supplementation in fattening sheep in the Piedemonte Llanero region of Colombia is a common practice to meet their nutritional needs due to climatic fluctuations and soil conditions. It is necessary to seek alternatives to preserve forage during summer to maintain its protein value. This study, conducted in Villavicencio, Meta, Colombia, aimed to evaluate the performance of crossbred fattening sheep grazing on Brachiaria spp. with supplementation of corn silage, palm kernel cake, wheat bran, and Tithonia diversifolia (Golden Button). The research was carried out at the University of los Llanos Farm in Villavicencio-Meta, using 12 sheep with an average weight of 19.5 ± 3.6 kg. At the start of the productive management, the sheep were administered Compleland B12 at a dose of 2 ml intramuscularly and dewormed with 1 ml of Febendazole at 25% orally. The sheep were allowed to graze Brachiaria spp. freely and were supplemented with 250 grams of dry matter per day, containing the following treatments: T1: 30% commercial concentrate (CC) + 70% corn silage (CS); T2: 30% CC + 40% CS + 30% palm kernel cake; T3: 30% CC + 40% CS + 30% wheat bran; T4: 30% CC + 40% CS + 30% Golden Button. The sheep were kept in stalls until 10 a.m. for supplementation and then taken out to graze. The analyzed variables included the nutritional content of the four treatments in terms of dry matter (DM), crude protein (CP), fat, crude fiber (CF), and non-nitrogen extract (NNE) in the supplied forages. DM, CP, organic matter (OM), and minerals such as Ca, Mg, P, and Cu were determined through foliar analysis. The sheep were evaluated for DM, CP, fat, CF, NNE consumption, in vivo digestibility of the DM of the supplied treatments, and weight gain. The statistical design was completely randomized, using Duncan's comparative test. For blood parameters, the Student’s T-test was used to measure before and after supplementation. The contents of DM, CP, OM, Ca, Mg, P, and Cu in the forages indicated that Golden Button (Tithonia diversifolia) has a good protein content of 17.39%, with higher (P
Keywords: blood biochemistry; production; ruminants; silage